2010
DOI: 10.1039/b924477h
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of macroscopic sessile droplets

Abstract: This review is aimed at presenting the evaporation of macroscopic sessile droplets on inert substrates in normal atmosphere in simple cases, as a basis for more complex analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
339
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 294 publications
(354 citation statements)
references
References 108 publications
(293 reference statements)
13
339
0
2
Order By: Relevance
“…While in this case it is often observed that drops are either pinned completely (i.e. the radius is constant, (Gelderblom et al 2011)) or perform a stick-slip motion (Cazabat & Guéna 2010), for our systems we observe the drop radius to shrink continuously during evaporation without pinning. We attribute this to our careful sample preparation, described in detail below.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…While in this case it is often observed that drops are either pinned completely (i.e. the radius is constant, (Gelderblom et al 2011)) or perform a stick-slip motion (Cazabat & Guéna 2010), for our systems we observe the drop radius to shrink continuously during evaporation without pinning. We attribute this to our careful sample preparation, described in detail below.…”
Section: Introductionmentioning
confidence: 81%
“…Since the speed of retraction is slow, as measured for example by the capillary number (Larson 2014), the dynamic contact angle is close to its constant equilibrium value, and the mode of evaporation is one of constant contact angle (Stauber et al 2015). As is well known (Cazabat & Guéna 2010;Stauber et al 2015), combining the evaporation rate (2.5) with the formula for the volume of a small (i.e. spherical cap-shaped) drop, one finds the drop radius to shrink like…”
Section: A Single Small Dropmentioning
confidence: 99%
See 3 more Smart Citations